PENGGUNAAN MODEL PEMBELAJARAN VAK (VISUAL, AUDITORY, KINESTETIK) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI ADAB MAKAN DAN MINUM - Mudhoffar Mudhoffar; Roihanah (Jurnal Penelitian Ilmiah INTAJ, 2021)
In Islamic religious education, teachers need to apply an appropriate and attractive learning model to increase student motivation and learning outcomes. Because there are various obstacles experienced by students, this research is important to do. This study aims to determine the use of the VAK learning model on the learning outcomes of class VIII students at SMP Mambaunnur Gading Bululawang. In implementing learning activities, teachers use various learning models, one of which is the VAK (visual, auditory, kinetic) learning model. This Learning Model emphasizes direct learning experiences by maximizing the ability to remember visually (Visual), auditory (Auditory), and increase movement and emotion (kinetic). This type of research is Classroom Action Research. This research was conducted in 2 cycles, namely cycle 1 and II. Each cycle is applied in one meeting. The implementation in each cycle uses four stages: planning, implementing, observing, and reflecting. The results of this study indicate that the use of the VAK learning model influences student learning outcomes. The increase in yield was seen in every cycle from pre-action to cycle II. Students who scored above the minimum completeness criteria (75) in the pre-action activity were 18%; about 5 students out of 27 students. In the first cycle the results showed a percentage of 40%; 11 students out of 27 students managed to show improvement. Whereas in cycle II the success of the method reached 100%, in other words 27 students experienced an increase in learning in the field of eating and drinking manners.